Behavioral activities and diet of Azaras's capuchin monkey, Sapajus cay (Illiger, 1815), in a forest remnant of the Brazilian Cerrado. (3rd May 2020) - Júnior, Oscar Fernandes; Porfirio, Grasiela Edith de Oliveira; Santos, Filipe Martins; Gimenes Nantes, Wesley Arruda; Oliveira de Assis, William; Braziliano de Andrade, Gisele; Herrera, Heitor Miraglia; Rímoli, José
ABSTRACT: Azaras's capuchin monkey ( Sapajus cay ) is a poorly studied species in ecological aspects. We investigated behavioral activities and diet of a group of S. cay in a remnant of the Brazilian Cerrado. We sought to identify the most frequent behavior that the group engaged in, as well as to verify possible differences in behavioral patterns and diet between adult males and females. From January to July 2012 we collected behavioral and foraging data for a group of 21 individuals using scan sampling. Behaviors and food items consumed were analyzed using percentages and two proportions Z-tests to assess differences between males and females. We obtained 878 scans in approximately 202 hours of sampling effort, resulting in 4, 159 individual activity records of capuchin monkeys. The group allocated time to traveling (41.3%), resting (25.5%), feeding (14.3%), foraging (13.7%), and social activities (5.1%). Females spent more time foraging and feeding, while males spent more time resting. Fruits (61.4%), invertebrates (15.3%), and seeds (14.3%) were the most common food items consumed. We did not find differences in food consumption between sexes. Behavioral activities may be influenced by habitat quality of the studied area, opportunistic habits, and plasticity in the diet.